Optimized Blanching Reduces the Host Cell Protein Content and Substantially Enhances the Recovery and Stability of Two Plant-Derived Malaria Vaccine Candidates - Menzel, Stephan; Holland, Tanja; Boes, Alexander; Spiegel, Holger; Bolzenius, Johanna; Fischer, Rainer; Buyel, Johannes F. (Frontiers in Plant Science, 2016)
Plants provide an advantageous expression platform for biopharmaceutical proteins because of their low pathogen burden and potential for inexpensive, large-scale production. However, the purification of target proteins can be challenging due to issues with extraction, the removal of host cell proteins (HCPs), and low expression levels. The heat treatment of crude extracts can reduce the quantity of HCPs by precipitation thus increasing the purity of the target protein and streamlining downstream purification. In the overall context of downstream process development for plant-derived malaria vaccine candidates, we applied a design-of-experiments approach to enhance HCP precipitation from Nicotiana benthamiana extracts generated after transient expression, using temperatures in the 20−80°C range, pH values of 3.0−8.0 and incubation times of 0−60 min. We also investigated the recovery of two protein-based malaria vaccine candidates under these conditions and determined their stability in the heat-treated extract while it was maintained at room temperature for 24 h. The heat precipitation of HCPs was also carried out by blanching intact plants in water or buffer prior to extraction in a blender. Our data show that all the heat precipitation methods reduced the amount of HCP in the crude plant extracts by more than 80%, simplifying the subsequent downstream processing steps. Furthermore, when the heat treatment was performed at 80°C rather than 65°C, both malaria vaccine candidates were more stable after extraction and the recovery of both proteins increased by more than 30%.